Opinions of the final year secondary health care students and the final year students of the undergraduate nursing study programme about organ donation - Đurić, Želimir (Array, 2019)
Aim. To examine and compare the opinions of the final year secondary health care students and the final year students of the undergraduate Nursing study programme about the significance of organ donation. Methods. A cross-sectional study was conducted on a sample of 60 participants of whom 30 were undergraduate Nursing study programme students and 30 were secondary health care students. The research instrument was a questionnaire designed for the purpose of this study, which included the following groups of questions: the first group consisted of questions about the participants’ general data, while the second group contained questions about organ donation itself. Results. From the obtained results, it was determined that there is no statistically significant difference in the decision to donate organs depending on the level of education. Furthermore, the results show that both groups of participants want to donate organs and the main motivation is to rescue someone’s life. In addition, the majority of participants express the view that such behavior is a humane act. Conclusion. Education level does not affect organ donation decision making. The main motivation for deciding on donating organs is to rescue someone’s life. Organ donation is an act of humanity. In the survey, several respondents expressed negative opinion about organ donation. Therefore, it is recommended that workshops aimed at future health professionals, be organized in secondary health care schools and other educational institutions for healthcare professionals to emphasize the importance of organ donation.